Legal Aspects of Extension of Time in PLN Transmission Construction Project in Central Sumatra: Bahasa Indonesia - Sungkara, Fajar; Sami'an, Sami'an; Hardjomuljadi, Sarwono (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Objective -This study aims to analyze the legal and contractual aspects related to the dispute over the extension of time in the PLN transmission project in Central Sumatra. This study focuses on the process, obstacles, and challenges faced in resolving the dispute. Methodology/Approach– The study uses a case study approach by analyzing contract documents, mediation processes, and related agreements between PLN and contractors. This study also examines the main elements of contracts within the Engineering, Procurement, and Construction (EPC) framework and evaluates the mediation process facilitated by the Financial and Development Supervisory Agency (BPKP). Findings– The results of the study showed that the delay in project completion, which was mostly caused by contractor inefficiency and external factors, resulted in disputes related to time extensions. Although contractors submitted justifications such as design changes, additional work, and external constraints, these reasons were considered inadequate by PLN. Mediation efforts provided a partial solution but also revealed systemic problems in contract management and dispute resolution mechanisms. Novelty/Benefits– This study contributes to the understanding of time extension disputes in large-scale infrastructure projects, and offers insights into effective dispute resolution strategies. The findings can serve as practical guidance for stakeholders in managing similar conflicts in the future while maintaining professional relationships.Keywords – Extension of time, Construction contract, Mediation,